Optimization of the functions of executive authorities of the Republic of Uzbekistan as a factor in improving the quality of public services - Kutibaeva Elizaveta Duisenbaevna; Shagilova Gulkhatisha Koptleuovna (Zien Journals, 2023)
Currently, in the Republic of Uzbekistan, the search for ways to increase the efficiency of the organization and functioning of the system of state bodies, the choice of their optimal model, the use of rational forms and methods of their impact on social processes is very relevant.
Keywords: rights and freedoms; citizens; standard of living